Cdc14 Phosphatases Preferentially Dephosphorylate a Subset of Cyclin-dependent kinase (Cdk) Sites Containing Phosphoserine - Bremmer, Steven C. (American Society for Biochemistry and Molecular Biology, 2012)
Mitotic cell division is controlled by cyclin-dependent kinases (Cdks), which phosphorylate hundreds of protein substrates responsible for executing the division program. Cdk inactivation and reversal of Cdk-catalyzed phosphorylation are universal requirements for completing and exiting mitosis and resetting the cell cycle machinery. Mechanisms that define the timing and order of Cdk substrate dephosphorylation remain poorly understood. Cdc14 phosphatases have been implicated in Cdk inactivation and are thought to be generally specific for Cdk-type phosphorylation sites. We show that budding yeast Cdc14 possesses a strong and unusual preference for phosphoserine over phosphothreonine at Pro-directed sites in vitro. Using serine to threonine substitutions in the Cdk consensus sites of the Cdc14 substrate Acm1, we demonstrate that phosphoserine specificity exists in vivo. Furthermore, it appears to be a conserved property of all Cdc14 family phosphatases. An invariant active site residue was identified that sterically restricts phosphothreonine binding and is largely responsible for phosphoserine selectivity. Optimal Cdc14 substrates also possessed a basic residue at the +3 position relative to the phosphoserine, whereas substrates lacking this basic residue were not effectively hydrolyzed. The intrinsic selectivity of Cdc14 may help establish the order of Cdk substrate dephosphorylation during mitotic exit and contribute to roles in other cellular processes.